Rating Agencies in Russia and their Influence on Subfederal Borrowing - O. I. Larina; N. V. Moryzhenkova (Управление)
In Russia, the topical issue today is the high volume of obligations of regions against the federal budget. These liabilities have been caused by the current crisis in the Russian economy as well as by the disproportionate economic development, and this issue requires an adequate solution. It is planned that later on the regions will develop market borrowings first of all in form of securities. This article analyzes the infrastructural component of the market of subfederal and municipal borrowings - rating agencies in Russia. The article is based on the actual official data characterizing the current state of the market of regional and municipal borrowings, data from credit rating agencies were used as well. There were used systems analysis method, comparative approach, and clustering method. The article results in the conclusion that ratings of the international agencies are not always unbiased politically, not economically, which negatively affects the development of the debt market as a whole and the market of subfederal and municipal bonds, in particular. The development of the Russian credit rating agencies has a number of advantages and will contribute to the development of the indicated market in the future.